EVALUATION OF OUTCOME OF 48 CASES OF LAPAROSCOPIC PYELOPLASTY AT TERTIARY CARE TEACHING HOSPITAL OF SOUTHERN RAJASTHAN - PANKAJ TRIVEDI,; VISHWAS BAHETI,; PUSHPENDRA CHOUDHARY, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to evaluate the outcome of 48 cases of laparoscopic pyeloplasty at a tertiary care hospital of Southern Rajasthan where medical facilities are still evolving. Methods: Data of 48 patients from the medical record department, who underwent laparoscopic pyeloplasty surgery in past 4 years (January 2019– January 2023) for primary ureteropelvic junction (UPJ) obstruction due to intrinsic UPJ abnormality or aberrant vessels, were analyzed retrospectively. Intraoperative findings, success rate, and complications were recorded. Results: Pelvic reduction was required in 30 (62.5%) patients. The mean operative time was 182.4 min and the mean blood loss was 55 mL. The mean hospital stay was of 4.2 days. Success rate of laparoscopic pyeloplasty was 97%. Over all 10.41% of patients had complications. Conclusion: Laparoscopic pyeloplasty deals concomitant secondary stones with less morbidity and complications. It has better cosmetic outcome as compared to open techniques and similar long-term success rates. Hence, it can be concluded that laparoscopic pyeloplasty is an excellent current gold standard for primary UPJ obstruction.